Phytoecdysteroids and flavonoid glycosides among Chilean and commercial sources of Chenopodium quinoa: variation and correlation to physicochemical characteristics - Graf, Brittany (J Sci Food Agric, 2015)
BACKGROUND: Little is known about varietal differences in the content of bioactive phytoecdysteroids (PE) and flavonoid glycosides (FG) from quinoa (Chenopodium quinoa Willd.). The aim of this study was to determine the variation in PE and FG content among seventeen distinct quinoa sources and identify correlations to genotypic (highland vs. lowland) and physicochemical characteristics (seed color, 100-seed weight, protein content, oil content). RESULTS: PE and FG concentrations exhibited over 4-fold differences across quinoa sources, ranging from 138 ± 11 μg/g to 570 ± 124 μg/g total PE content and 192 ± 24 μg/g to 804 ± 91 μg/g total FG content. Mean FG content was significantly higher in highland Chilean varieties (583.6 ± 148.9 μg/g) versus lowland varieties (228.2 ± 63.1 μg/g) grown under the same environmental conditions (P = 0.0046; t-test). Meanwhile, PE content was positively and significantly correlated with oil content across all quinoa sources (r = 0.707, P = 0.002; Pearson correlation). CONCLUSION: FG content may be genotypically regulated in quinoa. PE content may be increased via enhancement of oil content. These findings may open new avenues for the improvement and development of quinoa as a functional food.